Patient-controlled Intranasal Fentanyl Analgesia: A Pilot Study to Assess Practicality and Tolerability During Childbirth. Issue 1 (March 2016) - Kerr, D.; Taylor, D.; Evans, B.
Abstract : ( Int J Obstet Anesth. 2015;24(2):117–123) Labor pain is considered by many women to be one of the most painful experiences of their life. Available analgesic options include pharmacologic (systemic and neuraxial analgesia) and nonpharmacologic methods.